PELATIHAN DAN PENDAMPINGAN ANYAMAN ECENG GONDOK UNTUK PEMBERDAYAAN IRT: STUDI PKM DI DESA BUGEL, KULON PROGO - Riza Septriani Dwi; Danang Wahyudi; Yonata Buyung; Sumino Sumino; Aryo Anggorojati; Achmad Gilang Romadhon; Sarah Kasuhardi; Riski Kurniawan (Jurnal Abdi Insani, 2025)
Water Hyacinth (Eichhornia crassipes) is a tropical aquatic plant known for its extremely rapid growth, often regarded as a water weed due to its negative impacts on aquatic ecosystems. Nevertheless, this plant possesses significant potential as a raw material for handicrafts with economic value. This community service program (PKM) was conducted in Bugel Village, Panjatan Sub-district, Kulon Progo Regency, Special Region of Yogyakarta, with a dual purpose: to empower the local community by transforming water hyacinth into economically valuable craft products and, at the same time, to contribute to aquatic weed control. The primary target of the program was a group of housewives who had available time but were not yet engaged in productive activities, along with several active participants, including Hery Prazogie, Eko, Tolob, Susilo Edi, and Fauzi. The methods employed included program socialization, craft production training (covering drying techniques, material sorting, and weaving skills), basic business management training, as well as continuous mentoring and monitoring. The program was implemented over eight months, from January to August 2025. The results showed a significant improvement in participants’ skills. After three training sessions, most participants were already able to independently produce simple craft items. By the end of the program, more than 60 craft products had been successfully created, including bags, baskets, table mats, chairs, pencil holders, and various household accessories. Institutionally, the program led to the establishment of a small business group named Anyaman Bugel Mandiri “Independent Bugel Weaving”, serving as a collective platform for the community to develop creative economy-based enterprises. The program outputs also included scientific publications, promotional media (posters, features in local newspapers), and a documentary video, all of which strengthened the sustainability of the initiative. Overall, this activity demonstrates that water hyacinth once considered an environmental problem can be transformed into a new economic resource that supports the improvement of rural community welfare.